1973
DOI: 10.1136/bjo.57.10.728
|View full text |Cite
|
Sign up to set email alerts
|

Razor blade section in cataract surgery.

Abstract: There are many techniques of cataract extraction and many types of cataract knives have been devised to facilitate an ideal section. Ultrasharp diamond knives were introduced by Durham and Luntz (I968). Sharpness is essential whether the von Graefe knife, the keratome, or corneal scissors are used, and for this reason disposable cataract knives, keratomes, and Bard Parker blades are widely used.This article describes the use of an ordinary razor blade (preferably non-stainless); this is not only very sharp and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Current studies have shown that the postoperative astigmatism is influenced by the type of instruments used. [ 9 ] 4) Loops have been implemented as a means of partitioning the nucleus into separate pieces before delivering them out individually. This manuever will assist in delivering nuclei of varying densities through an incision of a predetermined size, which, in turn, may be helpful in standardizing the SIA.…”
mentioning
confidence: 99%
“…Current studies have shown that the postoperative astigmatism is influenced by the type of instruments used. [ 9 ] 4) Loops have been implemented as a means of partitioning the nucleus into separate pieces before delivering them out individually. This manuever will assist in delivering nuclei of varying densities through an incision of a predetermined size, which, in turn, may be helpful in standardizing the SIA.…”
mentioning
confidence: 99%